Genetically modified organisms : a guide to biosafety - Tzotzos, George T.; United Nations Industrial Development Organization; International Centre for Genetic Engineering and Biotechnology; C.A.B. International (Wallingford : CAB International, 1995)
For a number of years the promise of biotechnology has been dimmed by concerns over the intrinsic safety of transgenic organisms. Although considerable knowledge of the properties of recombinant systems and a vast volume of data gathered from different application of biotechnology are now available, these concerns are still evident. In the developing world, there are also fears that such countries might be used as testing grounds for recombinant products.
Considerations of this nature have often overshadowed the benefits these countries might derive from the application of genetic engineering.
In response to these concerns, UNIDO, together with the United Nations Environment Programme and the World Health Organization, formed in 1985 the Informal Working Group on Biosafety. In 1991 the Food and Agriculture Organization of the United Nations also joined the Group.
The present volume was commissioned by the Group and is intended to help scientists and regulators to conceptualize the major issues underlying biological safety as well as to understand how these affect policies to regulate biotechnology.
Ch. 1. Biological Risk Assessment: An Editorial Overview of Some Key Policy and Implementation Issues / George T. Tzotzos -- Ch. 2. Public Perception of Biotechnology / Marion Leopold -- Ch. 3. Risk Assessment and Contained Use of Genetically Modified Microorganisms (GMMs) / John Grinsted -- Ch. 4. Safety in the Contained Use and the Environmental Release of Transgenic Crop Plants / Philip J. Dale and Julian Kinderlerer -- Ch. 5. Environmental Release of Genetically Modified Rhizobia and Mycorrhizas / Geoffrey Hall -- Ch. 6. Microbial Pesticides: Safety Considerations / Morris Levin -- Ch. 7. Safety in the Contained Use and Release of Transgenic Animals and Recombinant Proteins / Don Powell -- Ch. 8. Safety Aspects of Aquatic Biotechnology / Raymond A. Zilinskas -- Ch. 9. Safety Considerations in Biotreatment Operations / Morris Levin.
Includes bibliographies and index.
Keywords: Transgenic organisms -- Safety measures -- Congresses; Recombinant microorganisms -- Safety measures -- Congresses; Genetic engineering